Analysis of Planning and Budgeting of Food and Animal Security Village Funds in Sukalaksana Village, Talegong District, Garut Regency - Putradi, Didit Fajar; Akbar, Gugun Geusan; Kania, Ikeu; Mulyaningsih, Mulyaningsih; Ulumudin, Aceng (Ann Publisher, 2025)
Background. The village fund's mandatory spending policy of 20% for food and animal security programs aims to encourage villages to develop resilient and adaptive local food systems. Implementing, planning, and budgeting food security programs at the village level still face a number of challenges, including Sukalaksana Village, Talegong District, and Garut Regency. Aims. The purpose of this study is to analyze the planning and budgeting of village funds and to analyze the impact of the implementation of food and animal security programs in Sukalaksana Village. Methods. The research method used is a qualitative approach with data collection techniques carried out through a Desk Study on the planning and budgeting documents of Sukalaksana Village and in-depth interviews. Result. The results showed that the planning and budgeting of village funds for food and animal security are based on priority needs, transparency, participation, and performance-based. Conclusion. The impact of the food and animal security program, in the form of farm roads and construction, increases food affordability through increasing food distribution and agricultural product transportation costs efficiency by 62.5%. Implementation. Provide substantial evidence for local governments that the allocation of Village Funds for food and animal security programs can have a real impact on the welfare of village communities if managed in a participatory and needs-based manner. Meanwhile, for the Village Government, this result reinforces the importance of compiling planning and budgeting documents that not only meet the administrative aspects but also focus on results and sustainability